Evaluation the Effectiveness of Interventions to Prevent Acute Respiratory Infection (Pneumonia) among Children under Five Year A Systematic Review - Ayudiah Uprianingsih, Ayudiah
Abstract: Pneumonia accounted for 15% of the 6.3 million deaths among children under the age of five years. It kills children more than any other illness. Each year, over 2 million children die from pneumonia, accounting for 1 in 5 under-five deaths worldwide. A variety interventions to prevent and to reduce pneumonia are available. This systematic review was carried out in order to inform and to know some interventions that can prevent pneumonia among children under five year. Methods : We identified articles through databases searching:, Proquest, Science Direct, SpringerLink, and Ebsco Host, published between (2002- 2017). Results: Ten articles were analysed and selected from 1271. Conclusions: The studied evaluated that the integration of the interventions such as hand washing, vaccination, exclusive breastfeeding, giving zinc supplement potentially be more cost-effective, efficient and sustainable. Other interventions that may be effective involve providing health education to family or c (More)